Patient profile and periprocedural outcomes of bioresorbable vascular scaffold implantation in comparison with drug-eluting and bare-metal stent implantation. Experience from ORPKI Polish National Registry 2014–2015 - Rzeszutko, Łukasz; Tokarek, Tomasz; Siudak, Zbigniew; Dziewierz, Artur; Żmudka, Krzysztof; Dudek, Dariusz (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2016)
Introduction: There are limited data on the comparison of bioresorbable vascular scaffold (BVS) and drug-eluting stent (DES)/bare-metal stent (BMS) implantation in an unselected population of patients with coronary artery disease. Aim : To compare the periprocedural outcomes and patient profile of BVS and DES/BMS implantation in an all-comer population from the ORPKI Polish National Registry. Material and methods: A total of 141,324 consecutive patients from 151 invasive cardiology centers in Poland were included in this prospective registry between January 2014 and June 2015. Periprocedural data on patients with at least one BVS (Absorb, Abbott Vascular, Santa Clara, CA, USA), DES or BMS (all available types) implantation in de novo lesions during index percutaneous coronary intervention for stable angina (SA) or acute coronary syndrome were collected. Results : Bioresorbable vascular scaffold was the most often used in patients with SA, in single-vessel disease and in younger male patients. Bioresorbable vascular scaffold implantation was significantly more often associated with periprocedural administration of ticagrelor/prasugrel (6.8% vs. 3.6%; p = 0.001) and use of intravascular ultrasound and optical coherence tomography in comparison with the DES/BMS group (2.8% vs. 0.6% and 1.8% vs. 0.1%, respectively; p = 0.001 for both). The incidence of periprocedural death was significantly lower in the BVS group than the DES/BMS group (0.04% vs. 0.32%; p = 0.02), but this difference was no longer significant after adjustment for covariates. On the other hand, coronary artery perforation occurred significantly more often during BVS delivery (0.31% vs. 0.12%; p = 0.01), and BVS implantation was identified as an independent predictor of coronary artery perforation in multivariate logistic regression analysis (OR = 6.728, 95% CI: 2.394–18.906; p = 0.001). Conclusions : Patients treated with BVS implantation presented an acceptable safety and efficacy profile in comparison with the DES/BMS group. However, lower risk patients were the most frequent candidates for BVS implantation.